Multiple Administrations of Itraconazole Increase Plasma Exposure to Pyrotinib in Chinese Healthy Adults - Liu Y; Zhang Q; Lu C; Hu W (Dove Medical Press, 2021)
Yueyue Liu, Qian Zhang, Chao Lu, Wei Hu Department of Clinical Pharmacology, The Second Hospital of Anhui Medical University, Hefei, 230601, People’s Republic of ChinaCorrespondence: Chao Lu; Wei HuDepartment of Clinical Pharmacology, The Second Hospital of Anhui Medical University, Hefei, 230601, People’s Republic of ChinaTel/Fax + 86-551 63806057Email 765385306@qq.com; huwei@ahmu.edu.cnPurpose: Pyrotinib, an irreversible human epidermal growth factor receptor 2 (HER2), is a epidermal growth factor receptor double-target tyrosine kinase inhibitor used for treating HER2-positive breast cancer. This study aimed to evaluate the impact of the strong CYP3A4 inhibitor itraconazole on the safety and pharmacokinetics of pyrotinib in Chinese healthy adults.Patients and Methods: This was an open-label, randomized, self-control study. Eighteen healthy adults were included in this trial. They received a single 80 mg dose of pyrotinib orally on days 1 and 9, and a 200 mg once-daily dose of itraconazole on days 6 through 22. Blood samples were obtained, and the drug concentration was detected using liquid chromatography/tandem mass spectrometry.Results: Compared with pyrotinib alone, the exposure to pyrotinib co-administered with itraconazole substantially increased, and the Cmax and AUC0-t increased by 2.78- and 10.8-fold, respectively. No serious adverse events were reported in this trial, and no participant dropped out of the trial because of adverse events.Conclusion: The exposure to pyrotinib was substantially affected by the action of itraconazole. The concomitant use of pyrotinib with itraconazole might require dose modification of pyrotinib. All treatments were well tolerated in healthy participants.Clinical Trial Registry: http://www.chinadrugtrials.org.cn/clinicaltrials.prosearch.dhtml, CTR20191866.Keywords: drug–drug interaction, itraconazole, pharmacokinetics, pyrotinib, safety